Allocation of Economic Competence in Teams: A Comparative Institutional Analysis - Pavel Pelikan (The Research Institute of Industrial Economics (IUI), 1997)
Attention is called to a little explored scarce resource, termed 'economic competence', which combines features of human capital and bounded rationality, and causes a singularity in resource-allocation in society. The performance of each economy is shown to strongly depend on how this resource is allocated, which in turn strongly depends upon the economy's institutions ('rules of the game'). Two stylized institutional variants of market selection and one of government selection are compared for their short-term and long-term effects upon the output and growth of a perfect team economy. The results are exemplified by throwing new light on the social value of financial markets and the limitations of industrial policies.
Keywords: D20; D92; H10; L52; O40; P51; 330; Economic competence; Human capital; Bounded rationality; Institutions; Entrepreneurs; Investors; Government; Market selection; Financial Markets; Industrial policies; Institutionalismus; Humankapital; Beschränkte Rationalität; Arbeitsgruppe; Theorie